Metal Vacancy Ordering in an Antiperovskite Resulting in Two Modifications of Fe2SeO. Issue 32 (16th June 2016) - Valldor, Martin; Wright, Taylor; Fitch, Andrew; Prots, Yurii
Abstract: Small, red Fe2 SeO single crystals in two modifications were obtained from a CsCl flux. The metastable α‐phase is pseudo‐tetragonal (Cmce, a =16.4492(8) Å, b =11.1392(4) Å, c =11.1392(4) Å), whereas the β‐phase is trigonal (P31, a =9.8349(4) Å, c =6.9591(4) Å)) and thermodynamically stable within a narrow temperature range. Both crystal structures were solved from twinned specimens. The enantiomers of the β‐phase appear as racemic mixtures. Selenium and oxygen form two individual interpenetrating primitive cubic lattices, giving a bcc packing. A quasi‐octahedrally coordinated iron atom is found close to the center of each surface of the selenium sublattice. The difference between the α‐ and β‐phases is the distribution of iron at 2/3 of the surfaces. α‐ and β‐Fe2 SeO are comparable with metal‐vacancy‐ordered antiperovskites. Each Fe/O lattice can also be described in terms of vertex‐sharing OFe4 tetrahedra, with a crystal structure similar to that of an antisilicate. Iron is divalent and has a high‐spin d 6 ( S =2) configuration. The β‐phase exhibits magnetoelectric coupling. Abstract : Two variants : Metal vacancy ordering in an antiperovskite results in two modifications of Fe2 SeO, which are pseudo‐tetragonal and chiral, polar, non‐centrosymmetric, and trigonal, respectively. Both modifications have similarities with ionic conductors. As the compounds seem to be insulating, the Fe is present as divalent high‐spin ions because of weak crystal fields.